417 An Athlete-Oriented Holistic Coaching Program Targeting Performance and Wellbeing in Neurosurgery Residents. (April 2023) - Schupper, Alexander J.; Carr, Matthew; Philbrick, Brandon; Chennareddy, Susmita; Kalagara, Roshini; Turner, Dan; Kellner, Christopher P.
Abstract : INTRODUCTION: Neurosurgery residency is a demanding environment, requiring high levels of performance endured over long periods of time. As a result, neurosurgery residency has been associated with significant rates of fatigue, depression, and physician burnout. To address this, the authors instituted a program within the residency, entitled the "Performance Protection Program, " consisting of a personalized program based on principles used with world-class extreme sports athletes designed for residents to achieve sustainably high levels of performance. METHODS: A 12-month coaching program was instituted by a performance coach within a single neurosurgery residency program. Residents attended individual and team-based monthly meetings, engaged in offsite team outings, and completed interactive reflective questions. The program focused on several pillars of performance excellence including mental, emotional, social, physical and physiological domains. RESULTS: Residents engaged in a total of 19 team sessions, 3 team outings, and over 87 individual sessions by mobile device or in-person during which they strategized with the coach on topics including: productivity, communication, regulating emotions under pressure, in-hospital nutrition, meal preparation, efficiency, accountability, posture and strength, job interviewing, confidence, visualization skills, and team leadership dynamics. By demand, a bi-weekly posture and mobility session was incorporated into the program. Early feedback demonstrated a need for adaptive strategies personalized to the resident's stage of training and life. Most residents expressed need for improvement in nutrition, physical wellness, and communication under fatigue. CONCLUSIONS: Neurosurgery residency is stress-provoking and arduous for trainees. To optimize resident performance while minimizing burnout, a curriculum based on principles in extreme sports was successfully enacted over a 12-month period. Other training programs may utilize similar interventions to promote resident well-being and improve mental and physiological states.